2002
DOI: 10.1016/s0022-5347(05)64724-6
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on therapy for vaginal endodermal sinus tumors

Abstract: Endodermal sinus tumor of the vagina is rare. All of our patients presented with painless bleeding of no obvious source. In such cases one must maintain a high index of suspicion for possible underlying pathological conditions even if ultrasound is negative. Evaluation must include endoscopic examination of the lower genitourinary tract. Bone marrow transplant should be considered as a last therapeutic resort in salvage cases of unresponsive vaginal endodermal sinus tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…A hobnail pattern, Schiller-Duval bodies, and the immuohistochemical demonstration of AFP have been recognized as histological features of EST [14]. Usually, in cases of EST of the vagina, it is necessary to perform vaginoscopy and vaginal biopsy under general anesthesia to make a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hobnail pattern, Schiller-Duval bodies, and the immuohistochemical demonstration of AFP have been recognized as histological features of EST [14]. Usually, in cases of EST of the vagina, it is necessary to perform vaginoscopy and vaginal biopsy under general anesthesia to make a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the advent of effective chemotherapeutic agents. Previous reports described that EST of the vagina, like gonadal EST [16][17][18], responded to combination chemotherapy, VAC (VCR, actinomycin-D, and CPA) [5,7], and cisplatin-containing combination chemotherapy that included BVP (cisplatin, bleomycin, and vinblastine sulfate) or PEB (cisplatin, VP-16, and bleomycin) [6,14]. Additionally, the success of chemotherapy has allowed a more conservative surgical approach to these tumors [9].…”
Section: Discussionmentioning
confidence: 99%
“…2 Only 8% of EST in females occur in the vagina. 3 Historically, the typical treatment protocol has consisted of operative excision with adjuvant radiation therapy and/or chemotherapy. More recently, cases have been reported that involve the use of chemotherapy alone, leaving surgical intervention as a last resort in an attempt to maintain fertility and sexual function for the future.…”
mentioning
confidence: 99%
“…More recently, cases have been reported that involve the use of chemotherapy alone, leaving surgical intervention as a last resort in an attempt to maintain fertility and sexual function for the future. [3][4][5][6] We present a case of vaginal EST in an infant where chemotherapy as a single modality of treatment has resulted in normalization of the serum alpha-fetoprotein (AFP) level, no pathologic evidence of malignancy confirmed by repeat vaginal biopsies, and potential preservation of sexual and reproductive function. To the best of our knowledge, of the known 69 cases of EST of the vagina reported in the literature, only 3 cases are reported to have used cisplatin, etoposide, and bleomycin (PEB) chemotherapy alone (Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation